Administrar, rendir y agotar el tiempo. Las jornadas de madres y padres universitarios - Arvizu Reynaga, Alma Vanessa (El Colegio de México A.C., 2020)
This text analyzes the use and distribution of time of university students who are also parents. The research was conducted at two higher education institutions, the Universidad Iberoamericana Campus Ciudad de México (UIA) and the Universidad Autónoma Metropolitana Unidad Cuajimalpa (UAM-C). Using the ethnographic method, a semi-structured interview was used to collect testimonies from 24 undergraduate students (men and women from both institutions). It was found that students triple-shift workday: family, school and working day. These days are closely linked to traditional gender roles and a sexual distribution of work.